The Role of the NTB Regional Research and Innovation Agency in Accompanying and Facilitating UMKM or Start-Ups in NTB - Putri, Bq. Ananta; Basuki, Prayitno (International Journal of Economics Studies, 2024)
Incubation is one strategy to develop UMKM or startups. Several local governments are trying to implement incubation programs to accelerate the emergence of new businesses in their areas. The West Nusa Tenggara (NTB) Provincial Government has formed a new institution called BRIDA (Regional Innovation Research Agency) which is tasked with handling the incubation process. The question that arises is whether this incubation process is in line with the existing incubation concept. This study uses a qualitative approach through interviews and observations at BRIDA NTB. This study involved interviews with BRIDA managers and tenant members there. The results of the study indicate that the incubation process at BRIDA is in accordance with startup incubation standards, namely BRIDA NTB provides a form of assistance by presenting experienced mentors in various fields, from formulating business ideas to implementing them in the field in covering various important aspects of business development. And BRIDA NTB provides facilities in the form of a place, processing business permits, and free business marketing networks. However, there are obstacles in the follow-up of startup businesses that are still unclear, as well as the limited budget of the local government which makes startup development less than optimal.